More Courage for Pension Policy! A Proposal - Stefan Voigt (Wirtschaftsdienst)
Abstract There is a broad consensus that Germany’s pension system needs substantial reform. However, politicians shy away from this because they are afraid that it will cost them re-election. Here, an independent ’pension council’ with far-reaching competences is proposed as a possible solution.